SKALA USAHA MINIMUM PADA USAHATANI TEMBAKAU (Nicotiana tabacum) KABUPATEN REJANG LEBONG - Utama, Satria Putra; Irawan, Andi; Marito H, Butmen (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2006)
Tobacco was one of priority commodity in Rejang Lebong district to develop, its supported by suitable micro climate and farmer behavior so long. The research were objected to analyze the influencing factors on produdion and minimum economic scale of tobacco farming system at Rejang Lebong District. These tried to answer thorugh the cob-douglas and break even point analyses. The research showed that area (x 1), TSP fertilizer (x3), ZA fertlizer (x4) significantly influence to tobacco production. Minimum economic scale of tobacco farming system around 0.07 ha but farmers scale about 0.49 ha. It meaned that farmet tobacco were already in comerdal/economic scale. Improving the prcxluction could be attained thorugh extensification and intesification . extensification in the way of extended the croping area, while intesification by improving fertilizers of TSP and ZA to optimal level of usage. others factors should be another farmer focus to increas prcxluction such quality of seed, integrated and environmental pestici e and so forth.